2015
DOI: 10.1007/s10096-015-2344-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential chitosan-coated alginate nanoparticles for ocular delivery of daptomycin

Abstract: Daptomycin may offer an antibacterial alternative for the treatment of endophthalmitis caused by methicillin-resistant Staphylococcus aureus (MRSA) and other potential agents. In the present project, mucoadhesive chitosan-coated alginate (CS-ALG) nanoparticles are proposed as an effective delivery system for daptomycin permeation across ocular epithelia, with potential for the treatment of bacterial endophthalmitis. CS-ALG nanoparticles were prepared by ionotropic pre-gelation of an alginate core followed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 37 publications
0
56
0
3
Order By: Relevance
“…The key features of a drug delivery system are biodegradability, biocompatibility, controlled drug transport, and delivery to the target tissue. 83 …”
Section: Np-based Antibiotic Delivery Systemsmentioning
confidence: 99%
“…The key features of a drug delivery system are biodegradability, biocompatibility, controlled drug transport, and delivery to the target tissue. 83 …”
Section: Np-based Antibiotic Delivery Systemsmentioning
confidence: 99%
“…Additionally, Hussein-Al-Ali et al reported strong antimicrobial potential of streptomycin-conjugated magnetic nanoparticles coated with chitosan against drug-sensitive S. aureus and its methicillin-resistant counterpart (MRSA), which might be a promising strategy to fight drug-resistant infections, particularity those reported in the hospital environment [46]. Recently, chitosancoated alginate (CS-ALG) nanoparticles were proposed for a facilitated ocular delivery system of daptomycin for the treatment of MRSA-originated endophthalmitis [49].…”
Section: Recent Advances In Application Of Antibioticconjugated Nanopmentioning
confidence: 99%
“…A preliminary review of the literature showed the possibility of encapsulation into alginate-chitosan nanoparticles of various chemical structures of antimicrobial compounds like: benzoyl peroxide [76], gatifl oxacin [77], levofl oxacin [78], daptomycin [79], nisin [80] (Figure 7) and Ocimum sanctum methanolic extract [81].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles were prepared using ionotropic gelation (with or without some modifi cations) [76][77][78][79][80][81], freezedrying and spray-drying methods [82]. In the majority of cases, the nanoparticles obtained by ionotropic gelation method are stables (zeta potential -ζ < -30 mV or ζ > +30 mV) [77,80,81], have a nearly spherical shape, with sizes ranging from < 100 nm [76,78,81] to 200-900 nm [77,79,80].…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation